Effect of biopreservative cultures on the shelf life of modified atmosphere packaged chicken cocktail sausage - Atas, Sevgi; Incili, Gokhan Kursad; Durmusoglu, Halil; Calicioglu, Mehmet (Tubitak Scientific & Technological Research Council Turkey, 2021)
The present study was undertaken to extend the shelf life of modified atmosphere packaged chicken cocktail sausages by using biopreservative cultures (Lactobacillus sakei (B-2) and Lactobacillus curvatus (B-LC-48)). According to the results, cocktail sausages in control group stored either at 4 degrees C or 10 degrees C were spoiled as of day 28 due to a decrease in average flavor score and general acceptance score and increases in mesophilic and psychrotrophic colony counts (p < 0.05). In bioprotective cultures treated groups, no spoilage was detected throughout the 60-day storage at 4 degrees C, whereas those products stored at 10 degrees C spoiled as of day 42. Results of this study indicated that the bioprotective cultures tested were able to control the spoilage bacteria by establishing bacterial predominance starting from the first day of the shelf life (p < 0.05). It was concluded that these cultures can be useful in chicken cocktail sausages production, especially when a proper cold chain cannot be guaranteed during transportation and at retail.
Keywords: Biopreservation; lactic acid bacteria; shelf life; chicken cocktail sausage; modified atmosphere packaging